2020
DOI: 10.1186/s12933-020-0988-9
|View full text |Cite
|
Sign up to set email alerts
|

Polygenic risk for coronary heart disease acts through atherosclerosis in type 2 diabetes

Abstract: Background: Type 2 diabetes increases the risk of coronary heart disease (CHD), yet the mechanisms involved remain poorly described. Polygenic risk scores (PRS) provide an opportunity to understand risk factors since they reflect etiologic pathways from the entire genome. We therefore tested whether a PRS for CHD influenced risk of CHD in individuals with type 2 diabetes and which risk factors were associated with this PRS. Methods:We tested the association of a CHD PRS with CHD and its traditional clinical ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 46 publications
1
18
0
Order By: Relevance
“…Therefore, while future innovation should go towards a better definition of cardiovascular risk (e.g. using genetic data) [ 31 , 32 ] and the precise definition of subjects who can take the most advantage from more intensive treatments [ 10 , 33 , 34 ], these needs go together with the one urgently advocating the correct application of current knowledge and therapeutic armamentarium. As previously estimated, implementing dyslipidemia guidelines into every day clinical practice would have a major impact on reduction of the occurrence of future cardiovascular events in patients with diabetes [ 1 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, while future innovation should go towards a better definition of cardiovascular risk (e.g. using genetic data) [ 31 , 32 ] and the precise definition of subjects who can take the most advantage from more intensive treatments [ 10 , 33 , 34 ], these needs go together with the one urgently advocating the correct application of current knowledge and therapeutic armamentarium. As previously estimated, implementing dyslipidemia guidelines into every day clinical practice would have a major impact on reduction of the occurrence of future cardiovascular events in patients with diabetes [ 1 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Type 2 diabetes is a multifactorial, typical complex disease, which is associated with lifestyle and other environmental factors [30,31]. In this research, a set of ten "real" hub genes, IL1B, ITGB2, ITGAX, COL1A1, CSF1, CXCL12, SPP1, FN1, C3, and MMP2, was integrated into a model to predict type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Further, we found no interaction effect between sex and PRS, and other studies have reported similar performance for CHD polygenic scores in both sexes. 23…”
Section: Discussionmentioning
confidence: 99%